Investigating Fisher effect in SACU countries: A wavelet coherence approach - Thando Mkhombo; Andrew Phiri (Cogent Economics & Finance)
The purpose of this study is to examine the time-frequency relationship in the Fisher’s effect for South African Customs Union (SACU) countries using continuous wavelet transforms. We use the Wavelet power spectrum to decompose the nominal interest rate and inflation rate across a time frequency space and then employ wavelet coherence tools to investigate the synchronization of the pair of time-series in a time-frequency space. The wavelet tools prove to be a powerful tool in harmonizing seemingly conflicting empirical evidences found in previous literature. Our findings indicate similar co-movement between interest rates and inflation for SACU countries in the post-2000 period, with stronger Fisher effects existing around the global financial crisis, and evidence of reverse lead-lag dynamics at higher frequencies during crisis period. However, subsequent to the crisis period lower frequency oscillation become increasingly dominant as higher frequency components lose their significance up until the COVID-19 pandemic when the high-frequency components re-appear. All-in-all, our findings have important academic and policy implications.